Responsabilidade civil do empregador pelos danos decorrentes de acidente do trabalho nas indústrias frigoríficas - Silva, Maria das Dores Araújo e (2017)
The main objective of this study was to verify the civil liability of the employer for the damages resulting from an accident at work in the meatpacking industry, with a view it‟s about the most serious violations of the health of the worker, most of which are irreversible. The theme was based on the Federal Constitution of 1988 and on human dignity. To this end, the following research problem was adopted: the right to health and quality of life of the worker, guaranteed by the Federal Constitution of 1988 as a fundamental right and consolidated in the recognition of the dignity of the human person, which constitutes one of the pillars of the Democratic State of Law, has been effectively implemented, especially in the case of workers in the meatpacking industry? In case of violation of this right, what is the way in which the employer should be held civilly liable for damages resulting from accidents at work? To this end, in the first chapter it‟s studied the work environment and worker health and safety, and the evolution of the right to health and the quality of life of the worker, today inscribed in Federal Constitutional of 1988 as a fundamental right. The main violations of this right have also been pointed out, especially with regard to workers in the meatpacking industry, environmental principles and some ILO Conventions on the subject. In the second chapter, the work accident was analyzed, considering the typical accident, occupational diseases and work accidents by equalization, pointing out the ones that are more frequent in the meatpacking sector. In the third chapter, the nuclear theme of the work was discussed, first introducing the introductory notions of civil responsibility. Next, checking the possibility of applying preventive civil liability in the work environment, based on the principles of prevention and precaution and focusing on the person of the worker, as an ideal treatment to avoid the realization of damages. It‟s pointed out as an example of the instruments of this prevention the implementation of a system of dangers and risks management in this environment. However, in view of the impossibility of reaching a zero risk, especially in contemporary society, in the case of the occurrence of damage, it‟s pointed out the reparatory civil liability and the coexistence in the Brazilian legal system of the application of subjective responsibility and objective liability, being verified evolution in the application of the objective responsibility one based on art. 927, sole paragraph, of Civil Code, of 2002. At the end of the third chapter, the application of this general clause to the damage caused to the working environment was analyzed, it‟s concluded that it‟s perfectly applicable to damages caused by accidents at work. Finally, with the support doctrinal, legal and jurisprudential foundations used during the research, as well as the analysis of paradigmatic cases, it‟s identified that specifically in relation to the meatpacking activity there was a significant advance in the reception and application of objective responsibility based on art. 927, sole paragraph, of Civil Code, of 2002, at the Superior Courts (“Tribunais Regionais do Trabalho” and “Tribunal Superior do Trabalho”), demonstrating that the position of the Superior Courts has sought to reflect the values of Brazilian Federal Constitution, of 1988, whose main pillar lies in the dignity of the human person. As for the study procedure, it‟s used bibliographical and documentary research, with data analysis in a qualitative and quantitative way, an investigative procedure that starts from the general to the particular one.